Acute effects of a single functional neurology session on autonomic modulation in a patient with mild depression: a case report - Clemente-Suárez, Vicente Javier; Escribano-Colmena, Guillermo; Navarro-Jiménez, Eduardo; Rey-Mota, Jorge (Frontiers in Neuroscience, 2025)
Autonomic dysregulation is frequently observed in individuals with psychological distress, including mild depression, anxiety, loneliness, and chronic pain. Functional neurology offers a non-invasive, sensorimotor-based approach aimed at restoring autonomic balance through targeted neural stimulation. This case report explores the acute effects of a single-session multimodal functional neurology intervention on heart rate variability (HRV) in a 38-year-old female patient presenting with mild depression, moderate anxiety, high loneliness, psychological inflexibility, and chronic musculoskeletal pain. Baseline psychological assessments were conducted to characterize the patient’s emotional and cognitive profile, but no post-intervention psychological data were collected. HRV was measured before and after the intervention using photoplethysmography, with time and frequency domain analyses performed. Post-intervention results showed an increase in high-frequency (HF) power and a decrease in low-frequency (LF) power, suggesting enhanced parasympathetic modulation. These findings provide preliminary physiological evidence that a brief neuromodulatory intervention may positively influence autonomic function. Further controlled research is warranted to assess the consistency and clinical significance of these effects.